Pengelolaan Perpustakaan sebagai Alternatif Penguatan Budaya Literasi di SD Muhammadiyah Sudagaran Wonosobo - Karima, Oktavia Nida (Universitas Negeri Surabaya, 2021)
The library is a means of supporting teaching and learning activities in schools because it stores library materials so that there needs to be good management so that it can be used as an alternative to strengthening literacy culture. This study aims to describe library management and the form of literacy activities that exist in the library of SD Muhammadiyah Sudagaran Wonosobo. This research is a qualitative research with the subject of the principal, librarian, teachers and students. The object of the research is library management and literacy activities in the library. Data collection techniques are indepth interviews, observation and documentation. Data analysis techniques are data collection, data reduction, data presentation, and drawing conclusions. The data validity test technique is source triangulation and technical triangulation. The results of the research on library management as an alternative to strengthening literacy culture in SD Muhammadiyah Sudagaran Wonosobo have been managed properly and optimally. Library management is carried out by planning, organizing, implementing and monitoring. The literacy activities in the library are reading, writing, scientific and mathematical literacy.